ASSESSMENT OF BUSINESS VALUE IN MODERN CONDITIONS - Shovkatov Nodirjon Ne’matjon ugli (International Journal of Innovations in Engineering Research and Technology, 2023)
Business valuation is one of the most popular services in valuation today. This is due to the fact that this type of information is necessary for owners to make such important decisions as: expanding their business, merging with other companies, investing, etc. According to average estimates, this procedure, once performed voluntarily by about ten percent of managers, is now performed on a voluntary basis in ninety percent of cases. Despite the prevalence and popularity of business assessment in this area, there are many problems caused by the imperfection of the legal framework in the country, the ambiguity of methodological approaches to assessment and their effectiveness. The article considers the main approaches (profitable, cost-based comparative, as well as the Olson and Black-Scholes model, the concept of economic profit) that are used in assessing the value of a business, describes their advantages and disadvantages, most of which are associated with their application without adaptation to the Uzbekistan business realities. The sequence of conducting the business evaluation procedure was studied and summarized, and the ratings of one of the agencies for the year were reviewed by individual indicators. In conclusion, brief conclusions on the results of the study of this issue are presented.